2013
DOI: 10.1038/gene.2013.5
|View full text |Cite
|
Sign up to set email alerts
|

Association of common single-nucleotide polymorphisms in innate immune genes with differences in TLR-induced cytokine production in neonates

Abstract: Significant variability in cytokine and chemokine expression after Toll-like receptor (TLR) stimulation has been observed between individuals. In this study, we determined the immunophenotypic variation in a cohort of 152 neonates associated with specific single-nucleotide polymorphisms (SNPs). We identified 23 SNPs in 12 genes of the innate immune system to be significantly associated with differential cytokine and chemokine production. SNPs in three gene families, namely STAT, IRF and SYK, accounted for most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 73 publications
1
16
0
Order By: Relevance
“…We have recently shown that variation in innate immune responses can be influenced by single nucleotide polymorphisms within the PRR pathways and that the prevalence of these single nucleotide polymorphisms varies within different racial backgrounds 39 . It is thus entirely possible that genetic differences (including variation in HLA) between our populations contributed to the differences in functional responses we measured between sites.…”
Section: Discussionmentioning
confidence: 96%
“…We have recently shown that variation in innate immune responses can be influenced by single nucleotide polymorphisms within the PRR pathways and that the prevalence of these single nucleotide polymorphisms varies within different racial backgrounds 39 . It is thus entirely possible that genetic differences (including variation in HLA) between our populations contributed to the differences in functional responses we measured between sites.…”
Section: Discussionmentioning
confidence: 96%
“…Responses to adjuvanted vaccines are also significantly affected by polymorphisms in innate immune receptors (e.g., TLR [ 200 ]) and/or other immune factors [ 200 , 201 ] and have not only been linked to autoimmunity (reviewed in [ 202 ]) but also been blamed for the failure of certain vaccines [ 203 ]. Cytokine expression levels are controlled by polymorphisms and for example in the case of IL-10, these polymorphisms have been shown to correlate with disease susceptibility (and likely also responsiveness to vaccines) when modeled in humanized mice [ 204 ].…”
Section: Off-the-shelf Vaccines Are Not For Everyone: Using Adjuvamentioning
confidence: 99%
“…1 A cohort study suggested that single nucleotide polymorphisms in Toll-like receptor response pathways are associated with the general increase in inflammatory cytokine production in subjects of Asian descent. 4 In summary, daily intensive dressing care has prevented our infant patient with KRT5 p.Glu477Lys mutation from developing lethal complications. Our case therefore offers hope to all GS-EBS patients with the same mutation and their caregivers.…”
mentioning
confidence: 97%